Do Strength and Anthropometric Size of the Lower Body Correlate with Serum Testosterone Levels? - Tae Yong Park; Moon Young Choi; Doohwan Kong; Jeong Kyun Yeo; Min Gu Park (The World Journal of Men's Health)
Purpose: Although lower body strength and size are often regarded as symbols of masculinity, their relationship to testosterone is unclear. This study aimed to determine the correlation between lower body strength, size, and testosterone levels. Materials and Methods: Serum testosterone levels, waist circumference, and body mass index (BMI) were measured in 69 men with erectile dysfunction (age >40 years). The circumferences of the thigh and calf were measured, and the muscle strength of the knee joints was evaluated using an isokinetic dynamometer. Patients were classified into three groups according to testosterone levels (group 1, <230 ng/dL; group 2, 230 to 350 ng/dL; group 3, >350 ng/dL). Differences in calf and thigh circumference, bilateral knee extension, and flexion strength between the three groups were investigated using a one-way analysis of variance. Pearson’s chi-square test was used to assess differences in lifestyle habits and underlying diseases. A partial correlation analysis was conducted to determine the association between testosterone levels and lower body size and strength. Results: There was no difference in BMI among the three groups, but waist circumference was significantly larger in group 1 than in groups 2 and 3. When comparing weight-adjusted values, bilateral thigh circumference showed a significant difference among the three groups. There was also a significant difference between the three groups in the weight-adjusted left calf circumference and in the weight-adjusted right knee extension strength. The partial correlation test showed a significant positive correlation between thigh and calf circumference values adjusted for weight and serum testosterone levels. Weightadjusted knee extension strength demonstrated a significant positive correlation with serum testosterone levels. Conclusions: Weight-adjusted thigh and calf circumferences, along with the thigh-to-waist ratio, showed a positive correlation with testosterone levels. Weight-adjusted knee extension strength was positively correlated with testosterone levels. Therefore, a robust thigh and strong lower body are related to testosterone.